2018
DOI: 10.5811/westjem.2018.11.39040
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Simulation vs. Standard Training for Teaching Medical Students High-quality Cardiopulmonary Resuscitation

Abstract: IntroductionMost medical schools teach cardiopulmonary resuscitation (CPR) during the final year in course curriculum to prepare students to manage the first minutes of clinical emergencies. Little is known regarding the optimal method of instruction for this critical skill. Simulation has been shown in similar settings to enhance performance and knowledge. We evaluated the comparative effectiveness of high-fidelity simulation training vs. standard manikin training for teaching medical students the American He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 44 publications
0
52
0
8
Order By: Relevance
“…The experimental and quasi-experimental designs were the most frequent in this review, standing out with levels of evidence of 2 and 3, respectively. This could be related to the need to compare the effectiveness of different methodological teaching strategies regarding CPR, for the choice of better practices (35) .…”
Section: Discussionmentioning
confidence: 99%
“…The experimental and quasi-experimental designs were the most frequent in this review, standing out with levels of evidence of 2 and 3, respectively. This could be related to the need to compare the effectiveness of different methodological teaching strategies regarding CPR, for the choice of better practices (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training for nurses gives benefits such as increased knowledge and skills and contributes to perceived readiness [29]. When comparing simulation training and standard training with cardiopulmonary resuscitation (CPR) with medical students, it has been shown that simulation training is superior [32].…”
Section: Discussionmentioning
confidence: 99%
“…325 Five studies showed improvement in CPR skills at the end of training with the use of feedback devices compared with no feedback device. 319,320,323,328,330 Two studies showed no difference in performance. 322,326 One study showed worse CPR performance at the conclusion of training, although this study has a high risk of bias because of unclear outcome definitions and the use of the audiovisual feedback system to replace an instructor.…”
Section: Cpr Performance From Training Conclusion To 1 Year Aftermentioning
confidence: 98%